2022
DOI: 10.1128/spectrum.01610-22
|View full text |Cite
|
Sign up to set email alerts
|

Human Clinical Isolates of Pathogenic Fungi Are Host to Diverse Mycoviruses

Abstract: Fungal pathogens of humans are a growing global health burden. Viruses of fungi may represent future therapeutic tools, but for many fungal pathogens there are no known viruses. Our study examined the viral content of diverse human-pathogenic fungi in a clinical biobank, identifying numerous viral genomes, including one lineage previously not known to infect fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Phylogenetic trees were reconstructed using the sequences of the P1, P2 or P3 proteins of the GaJV-1 and CaJV-1 or -2 reported here, and those of the closest viruses identified by BLASTP analysis in GenBank. These references include citrus virga-like and citrus jingmen-like viruses [ 16 ], grapevine-associated jiviviruses 1 and 2 [ 17 ] and some newly reported agents, such as mastic virus Y (MVY) identified in Pistacia lentiscus (MT334608-10), sisal-associated virgavirus B from the virome of sisal plants [ 30 , 31 ], soybean thrips Jivi-like viruses 1 and 2 from suction trap collected soybean thrips ( Neohydatothrips variabilis ) [ 32 ] and Aspergillus lentulus jivivirus 1 from a culture of the human fungal pathogen Aspergillus lentulus [ 33 ]. The tree for the RdRp encoding P2 protein is shown in Figure 5 while those for the P1 and P3 proteins are, respectively, shown in Figure 6 and Figure S3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic trees were reconstructed using the sequences of the P1, P2 or P3 proteins of the GaJV-1 and CaJV-1 or -2 reported here, and those of the closest viruses identified by BLASTP analysis in GenBank. These references include citrus virga-like and citrus jingmen-like viruses [ 16 ], grapevine-associated jiviviruses 1 and 2 [ 17 ] and some newly reported agents, such as mastic virus Y (MVY) identified in Pistacia lentiscus (MT334608-10), sisal-associated virgavirus B from the virome of sisal plants [ 30 , 31 ], soybean thrips Jivi-like viruses 1 and 2 from suction trap collected soybean thrips ( Neohydatothrips variabilis ) [ 32 ] and Aspergillus lentulus jivivirus 1 from a culture of the human fungal pathogen Aspergillus lentulus [ 33 ]. The tree for the RdRp encoding P2 protein is shown in Figure 5 while those for the P1 and P3 proteins are, respectively, shown in Figure 6 and Figure S3 .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a scenario in which these proteins could serve as adapters between a common partner and different cellular factors recognized by each viral protein, similar to the families of effectors expressed by fungal or bacterial pathogens to target host defense or sensing machineries, in particular through the ubiquitin-proteasome pathway [ 34 , 35 , 36 ]. Interestingly, datamining of the Aspergillus lentulus dataset from which AlJV1 had been identified (ERR7929648, [ 33 ]) allowed the identification, as well as the three known genomic RNAs of AlJV1, of two further contigs encoding proteins showing, respectively, homologies with the proteins P4 (e-value 7.4 × 10 −8 ) and P9 (e-value 5.9 × 10 −43 ) of GaJV-1. The protein with distant homology to GaJV-1 P4 shares the conserved domain identified in proteins P4, P5, P6, P7, P8 and P10 of GaJV-1 and shown in Figure 4 and also possesses the conserved nucleoside ribosyltransferase domain (pfam15891) present in GaJV-1 P4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycovirus-associated hypovirulence has also been proposed to be used as a therapeutic against human pathogenic fungal infections [ 8 – 10 ]. Recent studies have reported that human pathogenic fungal strains are hosts to diverse mycoviruses [ 11 ]. The process of controlling human pathogenic fungi would be similar to that of phage therapy, where bacteriophages are used to target and cure selective bacterial infections [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ∼5,500 RNA virus (kingdom Orthornavirae ) species currently represented in GenBank constitute just a tiny fraction of the estimated millions of RNA virus species on Earth (Geoghegan & Holmes, 2017; Kuhn et al, 2019; Dance, 2021; Harvey & Holmes, 2022). Recent high-throughput RNA sequencing (RNA-Seq) studies – performed with the express purpose of identifying RNA viruses – have revealed vast numbers of novel RNA viruses, and many new family-level virus clades in diverse eukaryotic host organisms (Cook et al, 2013; Li et al, 2015; Shi et al, 2016, 2018; Olendraite et al, 2017; Charon et al, 2020; Chiapello et al, 2020; Sutela et al, 2020; Wolf et al, 2020; Batson et al, 2021; Chen et al, 2022; Forgia et al, 2022a; Kinsella et al, 2022; Rosario et al, 2022; reviewed in Dolja & Koonin, 2018; Greninger, 2018; Obbard, 2018; Zhang et al, 2019; Cobbin et al, 2021; Harvey & Holmes, 2022). However, a much larger number of RNA-Seq studies are performed for projects that are unrelated to virus discovery, but instead aim to study the transcriptomes of the targeted cellular organisms.…”
Section: Introductionmentioning
confidence: 99%